Low Temperature Storage of Actinomycetes - Members of the Genus Streptomyces - O. N. Sineva; T. D. Ivankova; L. P. Terekhova (Антибиотики и Химиотерапия)
Studies have been carried out in the field of long-term storage of actinomycetes, representatives of the genus Streptomyces , at low temperatures (-70°C). It has been established that a high level of viability of the studied cultures of actinomycetes is maintained for 3 years the stability of the morphological characteristics of these cultures and the preservation of antibiotic activity against test microorganisms during the entire storage period are noted. Spores of streptomycetes retain a high level of viability, both with and without 10% glycerol solution as a cryoprotector. The effectiveness of spore preservation of genus Streptomyces actinomycetes by the method of low-temperature freezing is shown.